Evaluating digital nudge interventions for the promotion of cancer screening behavior: a systematic review and meta-analysis - Fangfang Wang; Yonglin Li; Chenxing Zhang; Rachel Arbing; Wei-Ti Chen; Feifei Huang (BMC Medicine)
Abstract Background Public adherence to cancer screening remains low and is influenced by both rational and non-rational factors, including decision biases that underestimate screening benefits. Digital nudge interventions have shown promise in promoting screening behaviors among at-risk populations, but systematic evidence is still lacking. This study aims to synthesize the effects of digital nudge interventions on promoting cancer screening behaviors in high-risk individuals. Methods A systematic search of 10 electronic databases was conducted, and studies published before April 1, 2024, were included. Eligible studies were randomized controlled trials (RCTs) that compared the effects of digital nudge interventions on cancer screening behavior with those of a control group and reported at least one outcome. The risk of bias was evaluated using the Cochrane Risk of Bias tool. Data on cancer screening uptake rates were pooled using a random-effects model. Subgroup analyses were performed for cancer types, intervention media, delivery conditions, and sensitivity. The study identified digital nudge strategies via the MINDSPACE framework and explored their influence on screening behavior through the HSM. Results Of the 14 randomized controlled trials included, 10 reported statistically significant results. The types of interventions in these studies were heterogeneous and available across multiple delivery channels based on the web, computer programmes, DVDs, telephones, patient navigation, or apps that tailored or served interactive information to participants to better understand screening risks and options. A random-effects model showed that digital nudge intervention strategies significantly improved adherence to cancer screening behavior (OR = 1.81, 95% CI = 1.35–2.44, p < 0.001). Differences between cancer types, intervention media, and delivery conditions were noted. Based on the MINDSPACE framework and HSM, eight nudge strategies were designed to promote screening behaviors, with the most common being the default strategy (n = 9). Most nudge tools were designed to leverage unconscious System 1 thinking, aiming to influence behavior in a more spontaneous and subtle way. Conclusions While digital nudge interventions have demonstrated significant positive effects in promoting early cancer screening participation among high-risk individuals, their impact varies. More robust research is needed to address methodological limitations and facilitate broader adoption and application of these interventions.